Acronyms, Shmacronyms (The Scientific World Journal)
Nature leads off this week with a story about a German proposal to build new collider for high-energy physicists named TESLA. Science leads with an article about a Soviet proposal to convert a former bioweapons lab called VECTOR into a center for virus research.